2017
DOI: 10.1056/nejmoa1700153
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccine Effectiveness in the United States during the 2015–2016 Season

Abstract: BACKGROUND The A(H1N1)pdm09 virus strain used in the live attenuated influenza vaccine was changed for the 2015–2016 influenza season because of its lack of effectiveness in young children in 2013–2014. The Influenza Vaccine Effectiveness Network evaluated the effect of this change as part of its estimates of influenza vaccine effectiveness in 2015–2016. METHODS We enrolled patients 6 months of age or older who presented with acute respiratory illness at ambulatory care clinics in geographically diverse U.S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
215
3
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 265 publications
(237 citation statements)
references
References 31 publications
11
215
3
1
Order By: Relevance
“…The dramatic difference between transcriptomic responses to the two vaccines and previous findings that children who received LAIV generated a less robust IgG antibody response than those who received IIV [8] provide new insights to help explain the lower vaccine effectiveness of LAIV observed during the 2015–16 influenza season [7]. Cao et al, found differential expression in the IIV group of plasma cell-mediated and inflammation genes, but in the LAIV group found IFN and cell-cycle-related transcripts [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The dramatic difference between transcriptomic responses to the two vaccines and previous findings that children who received LAIV generated a less robust IgG antibody response than those who received IIV [8] provide new insights to help explain the lower vaccine effectiveness of LAIV observed during the 2015–16 influenza season [7]. Cao et al, found differential expression in the IIV group of plasma cell-mediated and inflammation genes, but in the LAIV group found IFN and cell-cycle-related transcripts [11].…”
Section: Discussionmentioning
confidence: 99%
“…Certain IFN-related DEGs were also correlated with antibody response. We add to this important work of Cao et al, by including a larger sample size of children using data from the last season that LAIV was widely used and a season when LAIV did not perform well, as reported by the US Flu VE Network [7]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12] Subjects were classified according to age on September 1 st of each season (6 months to 8 years; 9 to 17 years; 18 to 49 years, 50 to 64 years; and 65 years or older) and receipt of current season’s influenza vaccine, as defined from administrative healthcare databases and state immunization registries. [15] We identified all ambulatory care visits for presumptive medically attended acute respiratory illness (ARI) based on International Classification of Diseases, Version 9, Clinical Modification (ICD-9, for encounters prior to 1 October 2014) and Version 10 (ICD-10, for encounters on or after 1 October 2014) codes (Supplemental Appendix). …”
Section: Methodsmentioning
confidence: 99%
“…H1N1, H3N2, and B influenza viruses, trivalent vaccines have been established to combat A (H1N1) pdm 09, H3N2 subtype, and B viruses [1]. Despite major vaccination efforts, antigenic variation occurring in epidemic seasons frequently reduces the efficacy of seasonal inactivated or live vaccines in Japan and the United States of America (USA) [2, 3]. For example, although 100% of children in primary and junior high schools in the southwestern region of Japan are vaccinated, large outbreaks have occurred in these schools, indicating that influenza virus variants quite different from the vaccine strains are prevalent in this area during the spring season [2].…”
Section: Introductionmentioning
confidence: 99%